1970
DOI: 10.1002/j.1551-8833.1970.tb03972.x
|View full text |Cite
|
Sign up to set email alerts
|

COAGULATION TESTING: A COMPARISON OF TECHNIQUES—PART 1

Abstract: Coagulation to remove particulate matter from turbid waters may be carried out by any of several techniques. This report attempts to discover which coagulation techniques yield comparable results, and which of these is preferable from the operator's standpoint. Because of its length, this report is divided in half. Part II, containing the results and a discussion, will appear in next month's issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…l Plot the values of K, as ordinate and In G as abscissa. The value of Ks at any G value normally follows a relationship of the form K, = k, In G + k2 (5) where k, and k, are constants for a particular water. The empirical relationship between the breakup constant Ks and velocity gradient G given in Eq 4 is merely for convenience in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…l Plot the values of K, as ordinate and In G as abscissa. The value of Ks at any G value normally follows a relationship of the form K, = k, In G + k2 (5) where k, and k, are constants for a particular water. The empirical relationship between the breakup constant Ks and velocity gradient G given in Eq 4 is merely for convenience in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…TeKippe and Ham, 106 in a comparative study of methods of coagulation testing, suggested that smaller floe particles probably have better filtration properties. This would eliminate the need for conventional flocculation prior to filtration, and make the rapid mixing process prior to direct filtration an important factor in determining filter efficiency.…”
Section: Point and Mode Of Application Of The Polymermentioning
confidence: 98%
“…More recent models utilize multiaperture operation" 4 with a pulse height analyzer (PHA) 126 and multichannel storage facility (MCA). 106 One disadvantage of the technique is the requirement for dilution of the suspension under investigation with a 1.0 M electrolyte (usually NaCl). This raises questions regarding the effect of ionic strength on particulates, especially in flocculated water.…”
Section: Electrical Resistance Measurements (Coulter Counter)mentioning
confidence: 99%
“…Black et al 1957), the jar test has remained the conventional method of understanding coagulation chemistry and optimizing flocculation mixing. A noted criticism of this ubiquitous tool relates to the reactor similitude to the true hydraulic conditions of fullscale coagulation/flocculation processes (TeKippe & Ham 1970). Although the use of traditional jar tests for flocculation control provide some indication of the appropriate type and concentration of flocculants, Argaman (1971) argued that pilot-plant studies are essential for assuring the success of the design of new plants.…”
Section: Introductionmentioning
confidence: 99%